Благословение: [роман] / Даниэла Стил ; пер. с англ. Е. Ивановой - Стил Даниэла (Романтическое настроение, 2013)
Экземпляры: К.Х. (20200311) / Инвентарный номер: 47715 / Цена: 112.50 / Сис.шифр: 84(7Сое) / Авт.знак: С 80 / ГРНТИ: 17.82 / ББК: 84(7Coe)